2021
DOI: 10.47176/mjiri.35.105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of secondary infections on the multidrug-resistant Tuberculosis: A cohort study

Abstract: Background: Tuberculosis (TB) causes over a million deaths annually and is still one of the most important public health problems worldwide. According to the World Health Organization estimates, the highest rates of TB in the European Region are in Tajikistan, Kazakhstan, Moldova, Kyrgyzstan, Romania, and Uzbekistan. The purpose of this study was to investigate the spectrum of nonspecific microorganisms isolated in patients with multidrug-resistant TB in Central Kazakhstan and to assess their suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…A comparison of the complex morphological study of pleural fluid biopsies and the molecular analysis of GeneXpert MBT/Rif pleural biopsies for the purpose of confirming the diagnosis of tuberculosis with other similar scientific studies of the early detection of MBT in patients with pleurisy showed high diagnostic efficiency of the Xpert MBT/Rif analysis. This molecular genetic analysis is simple and quick to use, unlike most complex morphological systems [30,31]. This study made possible to fully analyze the efficiency of the GeneXpert method in detecting MBT in patients with unknown pleural effusion, using the information resource of our own sample of patients.…”
Section: N Resultsmentioning
confidence: 99%
“…A comparison of the complex morphological study of pleural fluid biopsies and the molecular analysis of GeneXpert MBT/Rif pleural biopsies for the purpose of confirming the diagnosis of tuberculosis with other similar scientific studies of the early detection of MBT in patients with pleurisy showed high diagnostic efficiency of the Xpert MBT/Rif analysis. This molecular genetic analysis is simple and quick to use, unlike most complex morphological systems [30,31]. This study made possible to fully analyze the efficiency of the GeneXpert method in detecting MBT in patients with unknown pleural effusion, using the information resource of our own sample of patients.…”
Section: N Resultsmentioning
confidence: 99%
“…The field of machine learning has enormous potential to solve complex problems in various industries, and using deep neural networks, especially RNNs, is a promising area. Due to their ability to analyse sequential data and learn complex patterns, machine learning technologies have transformed areas such as speech recognition, natural language processing and handwriting recognition (13)(14)(15)(16) , enabling businesses to achieve greater efficiency and productivity. One of the most important developments in the field of machine learning is the emergence of deep neural networks, especially RNNs.…”
Section: Introductionmentioning
confidence: 99%